Declaration of Trust: A useful tool for the modern practice. (2nd March 2021) - Davison, Lisa
Abstract : Lisa Davison, Real Estate Partner from specialist healthcare law firm Hempsons, explains why a Declaration of Trust is vital to protect your surgery